2021
DOI: 10.1186/s43008-021-00055-1
|View full text |Cite
|
Sign up to set email alerts
|

IMA genome - F14

Abstract: Draft genomes of Penicillium roqueforti, Fusarium sororula, Chalaropsis populi, and Chrysoporthe puriensis are presented. Penicillium roqueforti is a model fungus for genetics, physiological and metabolic studies, as well as for biotechnological applications. Fusarium sororula and Chrysoporthe puriensis are important tree pathogens, and Chalaropsis populi is a soil-borne root-pathogen. The genome sequences presented here thus contribute towards a better understanding of both the pathogenicity and biotechnologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…When compared to other species of Chrysoporthe , namely C. austroafricana (44.67 Mb, 13,484 gene models), C. cubensis (42.62 Mb, 13,121 gene models), C. deuterocubensis (43.97 Mb, 13,772 gene models), and C. puriensis (44.66 Mb, 13,166 gene models), the genome size and predicted gene models of C. zambiensis were slightly larger, while the genome size and predicted gene models for C. syzygiicola were slightly smaller [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to other species of Chrysoporthe , namely C. austroafricana (44.67 Mb, 13,484 gene models), C. cubensis (42.62 Mb, 13,121 gene models), C. deuterocubensis (43.97 Mb, 13,772 gene models), and C. puriensis (44.66 Mb, 13,166 gene models), the genome size and predicted gene models of C. zambiensis were slightly larger, while the genome size and predicted gene models for C. syzygiicola were slightly smaller [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maximum-likelihood gene trees of the mating-type genes were generated using IQ-TREE v. 1.6.12 [ 35 ], using the built-in selection of the best evolutionary model. These analyses included mating-type gene sequences of C. puriensis [ 16 , 42 ], C. austroafricana [ 43 ], C. cubensis , and C. deuterocubensis [ 44 ], with Cry. parasitica [ 22 ] as an outgroup taxon.…”
Section: Methodsmentioning
confidence: 99%
“…This is also true for P. roqueforti. Recent analyses of several genomes from P. roqueforti revealed that depending on the strain, they contain between 34-37 biosynthetic gene clusters [10,109]. As it has been detailed in this review, to date, only six of these biosynthetic gene clusters have been experimentally linked to secondary metabolites produced by P. roqueforti.…”
Section: Future Challenges and Perspectives In The Study Of Secondary...mentioning
confidence: 96%
“…The laeA gene from the closely related species P. rubens (GenBank accession EU685842; [30]) was used to search for the laeA gene in the genome of P. roqueforti CECT 2905 [47] by BLASTN and BLASTX. The gene found and its deduced protein were named PrlaeA and PrLaeA, respectively (see Section 3).…”
Section: Search For the Prlaea Gene In P Roqueforti Cect 2905 And Seq...mentioning
confidence: 99%
“…To identify the PrlaeA gene in P. roqueforti CECT 2905, the laeA gene sequence from P. rubens [30] was utilized to perform BLASTN and BLASTX scans of the P. roqueforti CECT 2905 genome [47]. The search led to the identification of the PrlaeA gene, which is located on contig MSQC01000647.1 and spans nucleotides 44,522 to 45,800.…”
Section: Analysis Of the Prlaea Gene And Its Deduced Protein From P R...mentioning
confidence: 99%